Frailty Syndromes in Persons With Cerebrovascular Disease: A Systematic Review and Meta-Analysis - Palmer, Katie; Vetrano, Davide L.; Padua, Luca; Romano, Valeria; Rivoiro, Chiara; Scelfo, Bibiana; Marengoni, Alessandra; Bernabei, Roberto; Onder, Graziano (Frontiers in Neurology, 2019)
Background: Frailty can change the prognosis and treatment approach of chronic diseases. Among others, frailty has been associated with cerebrovascular diseases such as stroke. However, the extent to which the two conditions are related is unclear, and no systematic review of the literature has been conducted. Objectives: To conduct a systematic review and meta-analysis assessing the association of cerebrovascular diseases and frailty as well as prefrailty, in observational studies. The project was carried out on behalf of the Joint Action ADVANTAGE WP4 group Methods: The review was performed according to PRISMA guidelines. We searched PubMed, Web of Science, and Embase from 01/01/2002-26/05/2019. Pooled estimates were obtained through random effect models and Mantel-Haenszel weighting. Homogeneity was assessed with the I2 statistic. Publication bias was assessed with Egger’s and Begg’s tests. Results: Of 1027 studies searched, 18 studies were included. Stroke was the only cerebrovascular disease studied in relation to frailty syndromes. All studies except one reported an association between stroke and prefrailty or frailty. The pooled prevalence of prefrailty and frailty in stroke patients was 49% (95% CI=42-57) and 22% (95% CI=16-27), respectively. The pooled prevalence of stroke in prefrail and frail individuals was 4% (95% CI=2-5) and 10% (95% CI=6-13), respectively. The prevalence of frailty was twofold in persons with stroke compared to those without stroke (pooled odds ratio=2.32, 95%CI=2.11-2.55). Only two studies longitudinally examined the association between stroke and frailty, producing conflicting results. Conclusions: Frailty and prefrailty are common in persons with stroke. These results may have clinical implications, as they identify the need to assess frailty in post-stroke survivors and assess how it may affect prognosis. Longitudinal research that examines the temporal relationship between stroke and frailty are needed, as well as studies on other types of cerebrovascular disease.